STRATEGI KOMUNIKASI DALAM PENGUATAN KAPASITAS KELEMBAGAAN PADA PENGELOLAAN LAHAN GAMBUT MELALUI PENINGKATAN SUMBERDAYA MANUSIA DI SEKTOR PERTANIAN KALIMANTAN SELATAN - Hairi Firmansyah; Mira Yulianti; Muhammad Alif (Metacommunication, 2018)
AbstractResearch communication strategy in strengthening institutional capacity on peat land management through improving human resources in the agricultural sector in South Kalimantan has the aim of knowing the extent of the institutional role in peatland management in the agricultural sector, to identify the factors of communication that influence institutional capacity in peatland management in the agricultural sector .And analyze communication strategies to strengthen institutional capacity through increased human resources in the management of peatlands in the sector pertanian.Jumlah informants used in this study there are two groups of farmers, 1, Gapoktan, 1 Institutional Economics 2 Farmers and agricultural extension. Based on the obtained results of research activities that the farmer institutions have a role in solving problems of farmers farming, information dissemination and technology of farming, the cooperative farmer group members group members and a group of cooperation with other parties outside the group of farmers. All the factors that play a role in communication is the communicant, messages, media dankomunikan. And communication strategies to strengthen institutional capacity through improving human resources in peatland management in the agricultural sector is the increased support for agricultural extension as a communicator, an increase in the dynamics of the group as a study group and dissemination of agricultural information (media), diversification of sources of information and agricultural technology (material ) and increase the capacity of farmers in extension activities (communicant). Keywords: strategy, communication, roles, institutions, farmers' groups, farmers Abstrak.Penelitian strategi komunikasi dalam penguatan kapasitas kelembagaan pada pengelolaan lahan gambut melalui peningkatan sumberdaya manusia di sektor pertanian Kalimantan Selatan memiliki tujuan mengetahui sejauhmana peran kelembagaan pada pengelolaan lahan gambut di sektor pertanian, mengidentifikasi faktor-faktor komunikasi yang mempengaruhi kapasitas kelembagaan dalam pengelolaan lahan gambut di sektor pertanian.Dan menganalisis strategi komunikasi untuk memperkuat kapasitas kelembagaan melalui peningkatan sumberdaya manusia pada pengelolaan lahan gambut di sektor pertanian.Jumlah  informan yang digunakan dalam penelitian ini ada 2 kelompok tani, 1, Gapoktan, 1 Kelembagaan Ekonomi Petani dan 2 orang penyuluh pertanian.  Berdasarkan kegiatan penelitian di peroleh hasil bahwa kelembagaan petani memiliki peran dalam pemecahan masalah usahatani para petani, penyebarluasan informasi dan teknologi usahatani, tempat kerjasama anggota kelompok anggota kelompok tani dan tempat kerjasama kelompok dengan pihak lain diluar kelompok tani.  Semua faktor komunikasi yang berperan dalam adalah komunikan, pesan, media dankomunikan.  Dan strategi komunikasi untuk memperkuat kapasitas kelembagaan melalui peningkatan sumberdaya manusia pada pengelolaan lahan gambut di sektor pertanian adalah peningkatan dukungan penyuluh pertanian sebagai komunikator, peningkatan kedinamisan kelompok sebagai kelompok belajar dan penyebaran informasi pertanian (media), penganekaragaman sumber-sumber informasi dan teknologi pertanian (materi) dan peningkatan kapasitas petani dalam kegiatan penyuluhan (Komunikan). Kata kunci: Strategi, komunikasi, peran, kelembagaan, kelompok tani, petani